Effect of Surface Applied Crude Oil on Soil and Vascular Plant Root Respiration, Soil Cellulase, and Hydroxylase at Barrow, Alaska - Linkins, A.E.; Atlas, R.M.; Gustin, P. (ARCTIC, 1978)
Surface application of crude oil at 5 or 12 l/m² to polygonal coastal Arctic tundra altered microbial activity in all soil types during three summers after application. Respiration in 5 l/m² oil treated soils increased with decreases in cellulase activity (as endo- and exo-glucanase) and increases in aryl hydrocarbon hydroxylase indicating a shift in the catabolic base of soil microbiota. These trends were paralleled in the 12 l/m² soil, but usually after a lag period of one year, perhaps due to some toxic effect of the oil at high concentrations. These data suggest that tundra soil microbiota can actively modify oil and can utilize it to support metabolism. Higher respiration rates in oiled soils than in control soils suggest that soil microbiota degrade and utilize oil faster than the normal residual plant material